Pertanggungan jawab orang pribadi dalam Kejahatan Korporasi Perpajakan dalam pelanggaran menurut Hukum Pidana Pajak (Neolectura, 2026)
This study examines the liability of individuals in corporate tax crimes under Indonesian tax criminal law. The focus of the study is directed at the position of individuals, whether as taxpayers, corporate managers, authorized representatives, or parties who in fact possess the authority to determine corporate policies leading to tax crimes. The problems addressed in this research are how the form of criminal liability of individuals in tax crimes is regulated and how personal liability applies to individuals who are part of a limited liability company when tax violations occur. This research employs a normative legal method using statutory and conceptual approaches through an analysis of the Law on General Provisions and Tax Procedures, the Law on Harmonization of Tax Regulations, the Limited Liability Company Law, the New Criminal Code, and Supreme Court Circular Letter Number 4 of 2021. The findings show that criminal liability in the field of taxation is not only imposed on corporations, but may also be imposed on individuals who commit, order, participate in, or actually control tax criminal acts for the benefit of a corporation. Therefore, harmonization between tax law, criminal law, and company law is necessary in order to ensure legal certainty, justice, and effective tax law enforcement.